GEE Training Manual on Use of Earth Observation data and Google Earth Engine monitoring and early warning of floods and droughts in Zambia - Ghosh, Surajit; Alahacoon, Niranga; Amarnath, Giriraj (CGIAR System Organization, 2022)
This training manual supported participants in learning the pre-processing tool to provide the user with enhanced time-series processing capabilities and access to various open-source satellite data, learning basic scripts in Google Earth Engine for activities related to floods and drought in showcasing the application of water resource management. Specifically, the experts will give more focus to Google’s Earth Engine platform to showcase large- and small-scale scientific analysis and visualization of geospatial datasets. The codes and step by step procedure are given in the manual.